ICTV Virus Taxonomy Profile: Pospiviroidae - Di Serio, Francesco; Owens, Robert A; Li, Shi-Fang; Matoušek, Jaroslav; Pallás, Vicente; Randles, John W; Sano, Teruo; Verhoeven, Jacobus Th J; Vidalakis, Georgios; Flores, Ricardo; Ictv Report Consortium (Journal of general virology, 2021)
Members of the family Pospiviroidae have single-stranded circular RNA genomes that adopt a rod-like or a quasi-rod-like conformation. These genomes contain a central conserved region that is involved in replication in the nucleus through an asymmetric RNA-RNA rolling-circle mechanism. Members of the family Pospiviroidae lack the hammerhead ribozymes that are typical of viroids classified in the family Avsunviroidae. The family Pospiviroidae includes the genera Apscaviroid, Cocadviroid, Coleviroid, Hostuviroid and Pospiviroid, with >25 species. This is a summary of the ICTV Report on the family Pospiviroidae, which is available at ictv.global/report/pospiviroidae.
Keywords: RNA, Circular; RNA, Catalytic; genom virový; RNA virová; RNA katalytická; RNA, Viral; Genome, Viral; replikace viru; Virus Replication; viroidy; RNA; Viroids; kruhová RNA